FOXM1 overexpression is associated with adverse outcome and predicts response to intravesical instillation therapy in stage pT1 non-muscle-invasive bladder cancer - Breyer, Johannes; Erben, Philipp; Rinaldetti, Sébastien; Worst, Thomas (BJU international, 2019)
Objective: To investigate the role of forkhead box protein M1 (FOXM1) mRNA expression and its prognostic value in stage pT1 non-muscle-invasive bladder cancer (NMIBC). Patients and Methods; Clinical data and formalin-fixed paraffin-embedded tissues from transurethral resection of the bladder from patients with stage pT1 NMIBC, treated with an organ-preserving approach, were analysed retrospectively. Total RNA was isolated using commercial RNA extraction kits, and mRNA expression of FOXM1, MKI67, KRT20 and KRT5 was measured by single-step quantitative RT-PCR using RNA-specific TaqMan Assays. Statistical analysis was performed using Spearman's Rho, Wilcoxon or Kruskal–Wallis tests, Kaplan–Meier estimates of recurrence-free (RFS), progression-free (PFS) and cancer-specific survival (CSS) and Cox regression analysis. Results: Data from 296 patients (79.4% men, median age 72 years) were available for the final evaluation. Spearman correlation analysis showed that mRNA expression of FOXM1 was significantly correlated with MKI67 (ρ: 0.6530, P < 0.001) and with the luminal subtype, reflected by the positive correlation with KRT20 (ρ: 0.2113, P < 0.001). Furthermore, there was also a strong correlation of FOXM1 expression with adverse clinical and pathological variables, such as concomitant carcinoma in situ (P = 0.05), multifocal tumours (P = 0.005) and World Health Organization 1973 grade 3 disease (P < 0.001). Kaplan–Meier analysis showed overexpression of FOMX1 to be associated with worse PFS (P = 0.028) and worse CSS (P = 0.015). FOXM1 overexpression was also shown to be a predictive risk factor for CSS (hazard ratio 1.61 [1.13–2.34], L-R chi-squared: 7.19, P = 0.007). FOXM1 overexpression identified a subgroup of patients within the luminal subtype with worse RFS (P = 0.017), PFS (P < 0.001) and CSS (P = 0.015). Patients with low FOXM1 expression had better outcomes, irrespective of instillation therapy, whereas patients with high FOXM1 expression benefitted from intravesical chemotherapy with mitomycin C. Conclusion: High FOXM1 expression was associated with adverse clinical and pathological features and worse outcomes, and predicted response to intravesical instillation therapy in patients with stage pT1 NMIBC.
First published: 18 August 2018
Gesehen am 15.08.2019